A CRITICAL REVIEW OF COMMERCIAL PROPERTY FINANCING: THE POTENTIAL OF ISLAMIC FINANCING (International Journal of Islamic Business, 2017)
The construction sector in Malaysia grew at 8.1% from 2013 to 2016 supported by the growth in commercial property and the residential sectors at 12.5% and 9.8% respectively and has been on an increasing trend since the last four years (2013: 10.9%, 2014: 11.6%, 2015: 12.1 %, 2016: 10.3%) (Department of Statistics Malaysia, 2016). The Knight and Frank survey 2015 reported that commercial property financing comprised of 60% of properties priced at more than RM2 million and another 40% for properties priced below RM2 million. Commercial property prices have been on an increasing trend due to increased cost and interest rates as well as uncertain economic fundamentals. For Malaysia, interest rates (BLR) differ across banks ranging from 6.6% to 6.9% and the base rate (BR) ranges from 3.0% to 4.1% due to economic bubbles. Commercial property financing remains a vital issue for borrowers of both conventional and Islamic banks. For borrowers of conventional banks, an increase in interest rates means higher monthly installments which in turns may increase the default risk particularly in times of economic uncertainties. For borrowers of Islamic banks, although the financing is interest-free, the pricing of commercial property financing is still benchmarked against the conventional interest rates. This study highlights the problems that arise when Islamic financing still relies on the interest rates. In macroeconomic theory, financing strongly depends on the movement of the interest rates. In contrast, Islam prohibits interest due to the existence of price manipulations by some parties, considered as unfair, and the lack of risk- sharing mechanism. Therefore, this study seeks to gather opinions from Islamic scholars on the acceptability of using interest rates in determining commercial property rentals as well as identifying a potential Islamic financing model where the features of the potential Islamic financing model are discussed.